Assessing natural carbonation and service life prediction of supersulfated cement - Adrieli Brustolin; Caroline Angulski da Luz; Laura Silvestro; José Ilo Pereira Filho (Case Studies in Construction Materials)
An intensive investigation is being conducted on alternative binders due to the significant environmental impact of carbon dioxide emissions in the Portland cement (PC) manufacturing sector. Supersulfated cement (SSC) stands as an alternative cement composed of 70–90 % granulated blast furnace slag (GBFS), 10–20 % calcium sulfate (CS), and 5 % alkaline activator (AA). Hence, investigating durability, particularly under natural conditions like carbonation, is essential for understanding the performance of SSC, primarily due to its low alkaline reserve. This study assessed the compressive strength, void index, and natural carbonation of two SSC formulations composed of (i) 85 % GBFS and 10 % CS, and (ii) 75 % GBFS and 20 % CS, both with 5 % PC as AA. The alterations induced by carbonation in the mineralogy of SSC were further examined by X-ray diffraction (XRD) and thermogravimetric analysis (TGA). Moreover, an assessment of service life prediction adopting the Tutti model for carbonation was carried out. The SSC concrete samples exhibited 28-d compressive strength values of approximately 20 MPa. The SSC concretes exhibited a high susceptibility to carbonation, with carbonation depths of up to 7.3 mm after 28 weeks of exposure. The higher CS content in the SSC 75:20 sample resulted in the formation of gypsum and a lower content of ettringite, and after 28 weeks of exposure, the total carbonation of ettringite was observed, leading to a reduction in compressive strength of 25.7 %. By adopting a 50-year life cycle for initiating the corrosion process, elements with SSC concrete should be designed with a cover thickness of 60 mm, representing very high thicknesses for practical applications, which can make the material economically unfeasible.